2010
DOI: 10.1074/jbc.m110.108860
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma brucei Life Cycle Switch TbPTP1 Is Structurally Conserved and Dephosphorylates the Nucleolar Protein NOPP44/46

Abstract: Trypanosoma brucei adapts to changing environments as it cycles through arrested and proliferating stages in the human and tsetse fly hosts. Changes in protein tyrosine phosphorylation of several proteins, including NOPP44/46, accompany T. brucei development. Moreover, inactivation of T. brucei protein-tyrosine phosphatase 1 (TbPTP1) triggers differentiation of bloodstream stumpy forms into tsetse procyclic forms through unknown downstream effects. Here, we link these events by showing that NOPP44/46 is a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Analysis of the protein interfaces in the crystal lattice using PDBePISA[56] did not reveal any strong indications that the structures form a dimer in solution. Indeed, the elution profile from size exclusion chromatography demonstrated that TcPTP1 migrates as a monomer (data not shown), as was also observed for the classical PTPase from Tryapnosoma brucei , TbPTP1b[48]. Since the structures of chain A and chain B are very similar, the coordinates of chain A were used for structural analysis.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Analysis of the protein interfaces in the crystal lattice using PDBePISA[56] did not reveal any strong indications that the structures form a dimer in solution. Indeed, the elution profile from size exclusion chromatography demonstrated that TcPTP1 migrates as a monomer (data not shown), as was also observed for the classical PTPase from Tryapnosoma brucei , TbPTP1b[48]. Since the structures of chain A and chain B are very similar, the coordinates of chain A were used for structural analysis.…”
Section: Resultsmentioning
confidence: 68%
“…=1.0 Å over 274 aligned residues, 64% sequence identity, PDB code: 3m4u)[48] and human PTP1B (1.8 Å over 251 aligned atoms, 27% sequence identity, PDB code: 2hnq)[61]. Structural alignments of TcPTP1 and these two homologs reveal that the secondary structure elements align well with most of the structural deviations existing in the loops that connect them (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmepsin II (PMII) 1SME [224]; 1LEE, 1LF2 [225]; 1LF3, 1LF4 [226]; 2BJU [227]; 2IGX, 2IGY [228]; 3F9Q [229]; 1M43 [230]; 1ME6 [231]; 1W6H, 1W6I [232]; 1XDH, 1XE5, 1XE6 [233] Plasmepsin IV (PMIV) 1LS5 [225] Proline racemase (PRACA) 1W61, 1W62 [234] Protein Kinase 5 (PK5) 1OB3, 1V0O, 1V0P [235] Protein tyrosine phosphatase 1 (PTP1) 3M4U [236] 4AZ1 [237] Pteridine reductase 1 (PTR1) 2XOX [238] 1E7W, 1E92 [239]; 1W0C [240]; 2BF7, 2BFA,2BFM, 2BFO, 2BFP [241]; 2QHX, 3H4V [242] 2C7V [243]; 2WD7, 2WD8, 3GN1, 3GN2 [244]; 2VZ0 [245]; 3BMC, 3BMN, 3BMO, 3BMQ, 3JQ6, 3JQ7, 3JQ8, 3JQ9, 3JQA, 3JQB, 3JQC, 3JQD, 3JQE, 3JQF, 3JQG [246]; 2X9N, 2X9G, 2X9V, 3MCV [247]; 2YHI [248] Pteridine reductase 2 (PTR2) 1MXF, 1MXH [249] Purine nucleoside phosphorylase (PNP) 1NW4, 1Q1G [250]; 2BSX, 1SQ6 [251]; 3ENZ [252] Pyridoxal kinase (PdxK) 3ZS7 [253] Pyruvate kinase (PYK)…”
Section: Brucei T Cruzimentioning
confidence: 99%
“…The crosstalk of TbPTP1 and TbPIP39 can be abolished by the differentiation regulators citrate and cis-aconitate [190]. The crystal structure of TbPTP1 is available [192]. The activity of TbPTP1 is sensitive to ROS, and can be completely inhibited in vitro by 10 mM sodium orthovanadate (90% inhibition using 1 mM sodium orthovanadate), but not ≤50 mM sodium fluoride.…”
Section: Phosphatome Of Trypanosoma Bruceimentioning
confidence: 99%